2021
DOI: 10.1038/s41398-021-01646-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding complex functional wiring patterns in major depressive disorder through brain functional connectome

Abstract: Brain function relies on efficient communications between distinct brain systems. The pathology of major depressive disorder (MDD) damages functional brain networks, resulting in cognitive impairment. Here, we reviewed the associations between brain functional connectome changes and MDD pathogenesis. We also highlighted the utility of brain functional connectome for differentiating MDD from other similar psychiatric disorders, predicting recurrence and suicide attempts in MDD, and evaluating treatment response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 154 publications
(152 reference statements)
2
18
0
Order By: Relevance
“… 24 26 27 These regions are central to emotional regulation and self-reference and executive functions--all areas where deficits have been reported in MDD. 28 Consistent with previous studies, the patients with MDD noMF showed increased functional connectivity in these regions compared with HCs. 29 30 Moreover, patients with MMF displayed higher functional connectivity than the MDD noMF group, indicating MMF might be associated with worse emotional regulation skills.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 24 26 27 These regions are central to emotional regulation and self-reference and executive functions--all areas where deficits have been reported in MDD. 28 Consistent with previous studies, the patients with MDD noMF showed increased functional connectivity in these regions compared with HCs. 29 30 Moreover, patients with MMF displayed higher functional connectivity than the MDD noMF group, indicating MMF might be associated with worse emotional regulation skills.…”
Section: Discussionsupporting
confidence: 91%
“…The mPFC, PCC and pCunPCC are considered as core hubs of the DMN 24 26 27. These regions are central to emotional regulation and self-reference and executive functions--all areas where deficits have been reported in MDD 28. Consistent with previous studies, the patients with MDD noMF showed increased functional connectivity in these regions compared with HCs 29 30.…”
Section: Discussionsupporting
confidence: 77%
“…This abnormal link strength may be related to excessive brain network activation in patients processing information ( Rotenberg, 2004 ). Multiple studies have pointed out significant increases in the brain connections in patients ( Greicius et al, 2007 ; Goodman et al, 2021 ; Yang et al, 2021 ). In addition, depression is also considered as a “disconnection syndrome” ( Greening et al, 2014 ; Chen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the incidence of CVOD-related anxiety and depression is supposed to get more attention in clinical settings due to the link between anxiety/depression and negative outcomes, such as suicidality [ 16 ]. As indicated in a previous study that the neurobiological factors, neuro-immunological biomarkers, brain-derived neurotrophic factors, and other neuromodulators was found in suicidal behavior, ref.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in a previous study that the neurobiological factors, neuro-immunological biomarkers, brain-derived neurotrophic factors, and other neuromodulators was found in suicidal behavior, ref. [ 16 ] the CVOD-induced cerebral damage may not only cause anxiety/depression but also suicidality if the primary symptoms of anxiety/depression were not evaluated early enough.…”
Section: Introductionmentioning
confidence: 99%